(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Purpose: The retrograde flow of urine from the bladder to the upper urinary tract is known as vesicoureteral reflux (VUR). The association between VUR and UTI represents a significant threat to the kidney in the form of pyelonephritic scarring. Early diagnosis of reflux and identification of the pyelonephritic aggression are important for successful therapy. Purpose of this study is to find out the association between primary VUR and urinary tract infection. Objective: Early diagnosis of VUR presenting as UTI to prevent renal damage and also to asses the result of initial management of primary VUR. Materials and methods: From April 2004 to April 2005, 40 patients of documented UTI were evaluated with VCUG to demonstrate VUR in Dhaka Shishu Hospital. VUR grade III and above were further evaluated with DMSA renal scan to demonstrate renal scarring. Among reflux patients 6 patients underwent surgery (Cohen ureteric reimplantation), 8 patients were treated non-operatively and one patient died of renal failure. Non- VUR grouped patients were treated with antibiotic according to culture sensitivity report for 10 days. VUR patients were followed up for 12 weeks. Results: E.coli was the commonest organism causing UTI. Fifteen patients (38%) having different grades of primary VUR and it was more in male child and in below 1- year age group. Episodes of fever were the predominant clinical scenario followed by failure to thrive, loss of appetite, cloudy urine and frequent voiding. ARM was the commonest associated anomaly (27%). Conclusion: UTI especially in male child was associated with VUR in 38% of this study population. ARM was the common associated anomaly. Renal scarring was noted in higher grade of reflux. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19413